Implementasi Wearable Device pada Monitoring Suhu Tubuh, Denyut Jantung dan Saturasi Oksigen dalam Darah menggunakan Low Power Mode - Mahesha Bayu Paksi; Rizal Maulana; Eko Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Health is measuring the human condition itself based on mental and physical conditions. Health conditions can be determined by measuring their vital signs, namely heart rate and body temperature. One of the most important organs for humans that will be fatal if exposed to disease is the lungs. The use of wearable devices to check these important organs will be easy. The use of wearable devices that are used in daily activities will not last long if they use battery power. For this reason, the system utilizes the low power method to save the power used. This sleep mode feature will be implemented in a system that can monitor the state of the human body through temperature, heart rate and blood oxygen levels. In the heart rate reading test, the percentage of error during normal conditions is 9.42% and during exercise is 5.99%. In the temperature reading test, the error percentage is 2.44%. Sleep mode on the system is able to reduce current by 22.29% from 34.36 mA to 26.7 mA.